Design and VLSI Implementation of HighPerformance Face-Detection Engine using MCT (International Journal of Engineering and Computer Science, 2013)
In this paper, we proposes a work of fiction hardware architecture of face-detection engine for mobile applications. We used MCT(Modified Census Transform) and Adaboost learning technique as basic algorithms of face-detection authenthication in mobile applications. We have designed, implemented and verified the hardware architecture of face-detection engine for high-performance face detection and real-time processing. The face-detection chip is developed by verifying and implementing through FPGA. The developed ASIC chip has advantage in real-time processing, low power consumption, high performance and low cost which can be used as an authentication for the mobile applications. So we expect this chip can be easily used in mobile applications.